Does Green Product Innovation affect Performance of Saudi Chemical Industrial Firms? - Alsughayir, Abdulrahman (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2017)
Although many companies have recognized the concepts of environmental innovation, little research attention has been devoted to the consideration of relations between green product innovation and firm performance. This study aimed to investigate the impact of green product innovation on firms performance. A structured questionnaire was developed for the purpose of data collection, and 19 Saudi chemical firms were included. The data from each of the returned questionnaire were coded and entered into (SPSS) version 18.0 software, simple linear regression which was used for statistical analysis. Response rate was 89.4%. The results show that that green product innovation has a statistically significant impact on firms performance (calculated F was 91.7); with statistically significant at p < 0.00. These results can help companies involved in manufacturing green products to create a new environment and enhance their business performance.